On-chip platinum micro-heater with platinum temperature sensor for a fully integrated disposable PCR module - Sripumkhai, W.; Lekwichai, A.; Bunjongpru, W.; Porntheeraphat, S.; Tunhoo, B.; Ratanaudomphisut, E.; Kamsri, T.; Hruanun, C.; Poyai, A.; Nukeaw, J. (My University, 2010)
The on-chip platinum micro-heater prototypes for thermal cycling equipped with platinum temperature sensor are fabricated. The device has been designed, fabricated and characterized to explore the feasibility of the micro-heater for a fully integrated disposable lab-on-a-chip with the PCR module. The on-chip micro-heater demonstrates that the temperature transitions are shorter by comparison with the conventional PCR temperature routines. © (2010) Trans Tech Publications.
Keywords: Micro-heater; Polymerase chain reaction (PCR); RTD sensor